Study of cardiac disease and its outcome in pregnancy - Patel, Tejal L.; Pandey, Kritika S.; Ambaliya, Arvind (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Pregnancy comes as a temporary complication in the disease process of a patient with a cardiac lesion. It is the 4th common cause of maternal mortality and one of the most important non-obstetrical causes of maternal death. Previously most women with diagnosed heart disease were advised to avoid pregnancy and labor and termination was advised. But in modern obstetrical practice, pregnancy in a patient with a heart disease is no longer an unacceptable hazard. The objective of this study is to find out incidence of cardiac diseases in pregnancy, to evaluate their management and to find out maternal and fetal outcome in pregnancy with cardiac disease. Methods: This study is a prospective cohort study in which an analysis of maternal and fetal outcome in 30 cases of cardiac diseases in pregnancy was carried out in the department of Obstetrics and Gynaecology in our institute at Civil hospital Ahmadabad from 01/01/2017 to 31/12/2017.The study included all known case of RHD, CHD, or newly diagnosed case or surgically corrected case with prosthetic heart valves during current pregnancy. Results: Majority of women having pregnancy with cardiac disease were in the age group of 20-30 years. Majority of them were primigravida and suffered from rheumatic heart diseases with grade 1 NYHA severity. Majority of women got delivered by normal vaginal delivery with healthy fetal outcome. Most of the babies born to cardiac mother had their baby weight ranging between 2.0-2.5kg. Conclusions: The results of present study indicate that heart disease forms a considerable proportion of medical illness complicating pregnancy. Cardiac disease presents problems both to the obstetrician and as well as to the physician, cardiologist and to the neonatologist. But the majority of pregnancies complicated by heart disease are uneventful with a favorably good outcome for both the mother and the fetus.